Application of Nurse-led Family Participatory Rehabilitation Training in Early Rehabilitation of ARDS Patients with Mechanical Ventilation - Lu, Yingjin; Lu, Yanfang; Ji, Hongyun; Xu, Chaoyan; Wei, Chunxuan (Journal of Contemporary Medical Practice, 2025)
Objective: To explore the application effect of nurse-led family participatory rehabilitation training in early rehabilitation of ARDS patients. Methods: In this study, 62 patients with ARDS mechanical ventilation who met the criteria of admission and discharge in the intensive care unit of a tertiary hospital in Baise City from January 2024 to December 2024 were randomly divided into control group and experimental group, 31 cases in each group. The control group received ICU routine early rehabilitation, and the experimental group received nurse-led family participatory rehabilitation training. The differences in arterial blood gas analysis results, mechanical ventilation days, ICU hospitalization days, total hospitalization days, incidence of complications during hospitalization, and family satisfaction were compared between the two groups after intervention. Results: After intervention, PaO2 and OI in the experimental group were higher than those in the control group, PaCO2 was lower than that in the control group, and the difference was statistically significant (P<0.05). The mechanical ventilation days, ICU hospitalization days and total hospitalization days of the experimental group were shorter than those of the control group, and the differences were statistically significant (P<0.05). The incidence of complications in the experimental group was lower than that in the control group, the difference was statistically significant (P<0.05). The satisfaction of family members in the experimental group was higher than that in the control group, and the difference was statistically significant (P<0.05). Conclusion: Nurse-led family participatory rehabilitation training has a significant application effect in the early rehabilitation of ARDS patients with mechanical ventilation. It can improve the oxygenation and ventilation of patients, shorten the length of hospital stay, and improve the satisfaction of family members. It is worthy of promotion and application in clinical practice.